2014
DOI: 10.1016/s1499-3872(14)60297-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic distal pancreatectomy in Italy: a systematic review and meta-analysis

Abstract: BACKGROUND:The use of laparoscopic distal pancreatectomy (LDP) increased in the past twenty years but the real diffusion of this technique is still unknown as well as the type of centers (high or low volume) in which this procedure is more frequently performed. DATA SOURCE:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
(16 reference statements)
1
14
0
3
Order By: Relevance
“…2,3 Despite the lack of randomized clinical trials, clear advantages have been demonstrated in terms of pain, intraoperative blood loss, and length of hospital stay over the open approach, with comparable oncological outcomes. [4][5][6][7][8] Nevertheless, limits to the widespread adoption of LDP include 2D (2-dimensional) imaging, limited ergonomics, fulcrum effect, and the absence of tactile sensation.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Despite the lack of randomized clinical trials, clear advantages have been demonstrated in terms of pain, intraoperative blood loss, and length of hospital stay over the open approach, with comparable oncological outcomes. [4][5][6][7][8] Nevertheless, limits to the widespread adoption of LDP include 2D (2-dimensional) imaging, limited ergonomics, fulcrum effect, and the absence of tactile sensation.…”
Section: Introductionmentioning
confidence: 99%
“…4,8,15 However, few analyses have focused on a minimally invasive DP approach specifically for the treatment of PDAC. 2,5,[7][8][9][10]17,18 This study expands on the minimal data which have been published. In particular, this study is among the largest to compare the minimally invasive approach for PDAC to open surgery with the inherent value of ACS-NSQIP data augmented by pancreatectomy specific variables to more accurately assess early postoperative outcomes.…”
Section: Discussionmentioning
confidence: 80%
“…28 Previous studies have reported discrepancies regarding tumor size being either significantly smaller or equivalent in MISDP vs. ODP. 7,27 One outstanding point from the surgical pathology data was that stage IV consisted of 4% and unknown surgical pathology consisted of 5% of the patients in this series. The explanation behind the presence of resected stage IV disease can be attributed to two likely reasons, either DP completed prior to intraoperative recognition of metastasis or possibly some surgeons performing distal pancreatectomy with metastasectomy.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations